Physical Modeling of Flow Field inside Urban Street Canyons - Li, Xian-Xiang; Leung, Dennis Y. C.; Liu, Chun-Ho; Lam, K. M. (Journal of applied meteorology and climatology, 2008)
The flow characteristics inside urban street canyons were studied in a laboratory water channel. The approaching flow direction was horizontal and perpendicular to the street axis. The street width was adjusted to form street canyons of aspect ratios 0.5, 1.0, and 2.0. The velocity field and turbulent intensity were measured with a laser Doppler anemometer at various locations within the street canyons, which were used to elucidate the flow pattern inside the street canyons. It was found that the previous numerical modeling results are in good agreement with the current experimental results at most locations. For the street canyon of aspect ratio 0.5, which belongs to the wake interference flow regime, the mean and fluctuating velocity components were more difficult to measure as compared with the other two cases because of its more complicated flow pattern. Some guidelines for numerical modeling were developed based on the measurement results. The data presented in this paper can also be used as a comprehensive database for the validation of numerical models.